The Quality of Health Office Services in Serving the COVID-19 Vaccine to Community Satisfaction in Garut Regency - Taufik Nurul Ramdani (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2023)
The COVID-19 pandemic is one of the crucial health problems in Indonesia, so the government continues to strive to handle it, especially by vaccination. Vaccine administration is one of the preventive policies to minimize the spread of the virus. In Indonesia, the party in charge of holding the vaccination program is the Health Office. This makes the Health Office interact with the community. In exchange, of course, a relationship will be established. In this case, the community is the recipient, while the Health Office is the service provider. When someone receives a service, there will be satisfaction or even disappointment. Therefore, the researcher aims to review public satisfaction with the assistance of the Garut Regency Health Office when providing vaccinations. Then, researchers immediately made a study through quantitative methods by distributing a survey of 100 respondents using the purposive sampling method. This research questionnaire was distributed to vaccine service recipients at the Garut Regency Hall. The collected data was then analyzed using multiple regression with the help of SPSS 23 data processing tools. The results showed that three of the five service quality indicators affected community satisfaction. Indicators that affect public satisfaction include vaccine availability, vaccine information, and vaccination center infrastructure. Meanwhile, indicators for vaccinators and doctor behavior did not affect public satisfaction. Vaccine availability indicators are the most impactful part. Meanwhile, the behavior of doctors has the most negligible influence on community satisfaction. Keywords: Covid-19 pandemic; Quality of Service; Community Satisfaction